Noise absorption of gap graded mixtures with rubberized asphalt - Freitas, Elisabete F. (2009)
Sound absorption is a material property which contributes to reduce noise levels when sound propagates from the source to the receiver. Porous materials have particularly good absorption characteristics, not only because of the high percentage of air voids, but also due to their flow resistance and tortuosity. Road surface layers made of gap graded mixtures are among those absorptive materials. Because these mixtures have a void content that may be considered of medium level, this study aims to characterise their absorption capacity, particularly of those with rubberized asphalt binder. For this purpose, absorption measurements in a Kundt’s tube were performed on cores extracted from slabs with different gap graded asphalt. In order to study the effect of the rubberized asphalt, the mixtures were produced in laboratory with two types of rubberized asphalt and with unmodified asphalt. The effect of the binder was pondered with this procedure. Furthermore, the effect of porosity was considered bycomparing the results of mixtures which have considerably high and low void contents.